The strategic manager - Sminia, Harry 1963- (Routledge, Taylor & Francis Group, 2014)
"Strategy is something with which managers regularly engage throughout their working lives, yet it is often written and researched as though periodic box-ticking exercises are the only show in town. This textbook provides students and professionals with a solid understanding of the strategic management theories, along with the tools needed to apply them and contribute toward successful organizations" - Provided by Publisher